Motivasi Karyawan Dalam Meningkatkan Produktivitas Kerja Karyawan Pada UMKM Martabak - Reza Amalia Putri; Lisnawati L; Dwi Epty Hidayaty (Yayasan Daarul Huda Kruengmane, 2023)
This article aims to find out how employee motivation increases employee work productivity at UMKM Martabak. Work productivity is greatly influenced by employee motivation, this is related to encouragement, attitude, and enthusiasm that comes from within the human person. High or low employee motivation affects the productivity of employers. The purpose of writing this article is to find out the importance of work motivation in increasing employee work productivity. Motivation plays a significant role in influencing and increasing work productivity, employees will work with discipline and diligence. But apart from that, the lack of appreciation, salary, and bonuses can also reduce employee motivation. This decreased motivation greatly affects the increase in work productivity, which in turn can make a business decline. Suggestions for business owners to be more aware and pay more attention to their employees in order to maintain work motivation and establish positive relationships between superiors and subordinates.